ANALYSIS OF THE COST OF HARVEST PREMIUM FOR PALM OIL PLANTATIONS PT. SURYA PANEN SUBUR. 2 IN AFDELING BRAVO - Widia Citra; Yoga Nugroho (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
PT Surya Panen Subur 2. Is one of the oil palm companies that cultivates fresh fruit bunches of FFB which are processed into CPO (Crude Palm Oil) which has a land area of ​​5,080.00 Ha. Which consists of several Afdeling one of which is Afdeling Bravo. The purpose of the harvest premium cost analysis is to explain harvesting activities,explaining harvest planning, as well as calculating and analyzing the cost of oil palm harvester premiums in Afdeling Bravo. The analytical method used is quantitative analysis and qualitative analysis based on results and discussion. Harvesting activities consist of daily harvest plans for cutting fresh fruit bunches, harvesting process, harvest premium system, harvest cost analysis, premium cost analysis, total premium cost and harvest income. The planned production target in August is1,531,960 kg and the total production after planning is 1,531,960 kg and the costs incurred by the company are Rp. 151,427,158-, withthe total income of harvesters in the Bravo section is Rp. 154,655.65,-